2023
DOI: 10.3389/fmed.2023.1140100
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic, clinical, and serum markers may improve discrimination between bacterial and viral etiologies of childhood pneumonia

Abstract: BackgroundDiscrimination of bacterial and viral etiologies of childhood community-acquired pneumonia (CAP) is often challenging. Unnecessary antibiotic administration exposes patients to undue risks and may engender antimicrobial resistance. This study aimed to develop a prediction model using epidemiological, clinical and laboratory data to differentiate between bacterial and viral CAP.MethodsData from 155 children with confirmed bacterial or mixed bacterial and viral infection (N = 124) and viral infection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Some studies show that combining clinical symptoms and blood biomarkers can improve discrimination between bacterial or viral CAP in children. For example, high CRP with fever increased specificity in distinguishing bacterial and viral pneumonia when compared to elevated CRP alone [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that combining clinical symptoms and blood biomarkers can improve discrimination between bacterial or viral CAP in children. For example, high CRP with fever increased specificity in distinguishing bacterial and viral pneumonia when compared to elevated CRP alone [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified into viral and bacterial/mixed pneumonia based on serum levels of PCT, neutrophil counts and CRP values. Because it is well documented that serum levels of CRP and PCT, and neutrophil counts were higher in bacterial/mixed cases than viral cases in pediatric pneumonia although they are not yet used in clinical routine [ 9 11 ]. Moreover, it has previously been suggested that pneumonias with serum PCT > 800 pg/ml (= 0.8 ng/ml) can be classified as bacterial/mixed, while those with PCT < 800 pg/ml can be classified as viral [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…In another meta-analysis involving 35 studies and including 6686 COVID-19 patients, the overall incidence of gastroenterological symptoms was 15% [ 97 , 98 ]. Similarly, in a study of 124 children with CAP, diarrhea symptoms were present in about 24% and vomiting in 7.3% of cases [ 99 ]. On the other hand, patients suffering from Inflammatory Bowel Disease (IBD) had an increased prevalence of severe COVID-19 and bacterial pneumonia [ 100 , 101 ], and their risk of complications is also significantly increased [ [101] , [102] , [103] ].…”
Section: Gut-lung Axis and Pneumoniamentioning
confidence: 98%